2016
DOI: 10.1128/jcm.03022-15
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Staphylococcus aureus Virulence and Resistance Genes: a Comparison of Whole-Genome Sequencing and DNA Microarray Technology

Abstract: Staphylococcus aureus is a major bacterial pathogen causing a variety of diseases ranging from wound infections to severe bacteremia or intoxications. Besides host factors, the course and severity of disease is also widely dependent on the genotype of the bacterium. Whole-genome sequencing (WGS), followed by bioinformatic sequence analysis, is currently the most extensive genotyping method available. To identify clinically relevant staphylococcal virulence and resistance genes in WGS data, we developed an in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Other previous studies have shown 100% concordance between the resistome and toxome in 14 MRSA isolates (24), 98.6% concordance across 5,288 susceptibility predictions in 308 S. aureus isolates (both MRSA and MSSA) (25), 100% concordance for selected resistance and toxin gene presence/absence in 18 MRSA strains (23), and 97% and 97% sensitivity and specificity, respectively, for Typewriter and 99.1% and 99.6% sensitivity and specificity, respectively, for Mykrobe for predicting phenotypic resistance in the Oxford validation samples used here (9,10). A comparison between microarray and WGS in 154 isolates reported 1.7% discordancy in detecting resistance and virulence genes (26), mainly due to the failure of WGS to detect enterotoxins and super antigens (similar to that for Typewriter in this study).…”
Section: Discussionmentioning
confidence: 99%
“…Other previous studies have shown 100% concordance between the resistome and toxome in 14 MRSA isolates (24), 98.6% concordance across 5,288 susceptibility predictions in 308 S. aureus isolates (both MRSA and MSSA) (25), 100% concordance for selected resistance and toxin gene presence/absence in 18 MRSA strains (23), and 97% and 97% sensitivity and specificity, respectively, for Typewriter and 99.1% and 99.6% sensitivity and specificity, respectively, for Mykrobe for predicting phenotypic resistance in the Oxford validation samples used here (9,10). A comparison between microarray and WGS in 154 isolates reported 1.7% discordancy in detecting resistance and virulence genes (26), mainly due to the failure of WGS to detect enterotoxins and super antigens (similar to that for Typewriter in this study).…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to true variations in the core genome or is related to technical issues. The latter, however, is unlikely, as the same bioinformatics algorithm has been applied and successfully validated with DNA microarray data ( Strauss et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the non-detection of genes does not necessarily prove their biological absence, but may also be caused by technical limitations of shotgun sequencing and de novo assembly. However, the technical error rate of WGS was shown to be < 2% ( Strauss et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations